EDITORS’ COMMUNICATION PATTERNS IN THE PROCESS OF BOOK MANUSCRIPTING AT POLIMEDIA PUBLISHING - Diah Amelia (Ikatan Sarjana Komunikasi Indonesia, 2017)
Editors have a responsibility for editing the manuscripts. Editing is a process to improve a manuscript to be eligible for publication. The purpose of this study is to understand and describe the communication patterns of editors. Editors must communicate with the authors, publishing companies, and readers. This study may help to understand and describe the editors' communication patterns, including the influence of knowledge and education in the process of work. This study is a qualitative study using phenomenological study that seeks the essence of the meaning of phenomena experienced by some individuals. Researcher can conduct communication research and examine the symptoms of humanities. Informants in this study are editors at Polimedia Publishing which is one of university publishers. The theory used is interpersonal communication supported by the editor knowledge which explains on a mutual communication between editors and authors as well as publishers. The result of the study is that an editor should have specific communication patterns, knowledge and a proper education in completing a manuscript as a part of literacy.